The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1163/156851605775009483
|View full text |Cite
|
Sign up to set email alerts
|

Hope, Critique, and Utopia

Abstract: This paper assesses the extent to which the category of hope assists in preserving and redefining the vestiges of utopian thought in critical social theory. Hope has never had a systematic position among the categories of critical social theory, although it has sometimes acquired considerable prominence. It will be argued that the current philosophical and everyday interest in social hope can be traced to the limited capacity of liberal conceptions of freedom to articulate a vision of social transformation app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…The concept of social hope is fundamental to many versions of critical social theory and to utopian philosophizing in particular (e.g., Bloch, ; Browne, ; Levitas, ; Morgan, ; Rorty, ). As in Gramsci's notion of “optimism of the will,” collective experiences of hope are thought to link subjective and objective processes of reality construction, ideology, and praxis:
The hope I am concerned with is not merely an attitude, or a mood, or a feeling—all of which emphasize its subjective side.
…”
Section: A Social Psychological Framework For Studying the Effects Ofmentioning
confidence: 99%
“…The concept of social hope is fundamental to many versions of critical social theory and to utopian philosophizing in particular (e.g., Bloch, ; Browne, ; Levitas, ; Morgan, ; Rorty, ). As in Gramsci's notion of “optimism of the will,” collective experiences of hope are thought to link subjective and objective processes of reality construction, ideology, and praxis:
The hope I am concerned with is not merely an attitude, or a mood, or a feeling—all of which emphasize its subjective side.
…”
Section: A Social Psychological Framework For Studying the Effects Ofmentioning
confidence: 99%
“…Operating as ‘visions of hope’ (McKenna, 2001), it is suggested that utopian ideas can serve to cultivate new ‘movements of hope’ (Fournier, 2002). Confronted with contemporary suffering and injustice, utopianism is widely heralded as a means of recapturing the category of hope for critical social theory (Anderson, 2006; Browne, 2005).…”
mentioning
confidence: 99%
“…The literature on each of these points is now prolific; however, for work on the polarisation of inequality see Harvey (2007); on the 'mediapolis', Silverstone (2007); on new forms of exclusion, Waquant (2007); on de-democratisation, Brown (2003); and on the corporatisation of higher education, see the excellent bibliography at Storm Breaking upon the University (http://stormbreaking.blogspot.com/) 5. For other accounts of the 'crisis of hope' in late-capitalist society, see Bauman (2004), Browne (2005), Giroux (2004Giroux ( , 2007, Habermas (1989), Harvey (2005), Jameson (2004and Zournazi (2002. 6.…”
Section: Resultsmentioning
confidence: 99%